Growth, meat and feed efficiency traits of lambs born to ewes submitted to energy restriction during mid-gestation - Piaggio, L.; Quintans, G.; San Julián, R.; Ferreira, G.; Ithurralde, J.; Fierro, S.; Pereira, A. S.C.; Baldi, F.; Banchero, G. E. (Elsevier, 2018)
The objective of this study was to evaluate the effects of the energy restriction of gestation of adult ewes from day 45 to day 115 on lamb live performance parameters, carcass and meat traits. In experiment I, dietary energy was restricted at 70% of the metabolizable energy (ME) requirements, after which ewes were re-fed ad libitum until lambing. In experiment II, dietary energy was restricted at 60% of the ME requirements, and ewes were re-fed to ME requirements until lambing. All ewes grazed together from the end of the restriction periods to weaning. Lambs were weaned and lot fed until slaughter. Feed intake, weight gain and feed efficiency were recorded, and body fat thickness and ribeye area (REA) were measured in the longissimus thoracis muscle. After slaughter, carcass weight and yield, fat depth, carcass and leg length, and frenched rack and leg weights and yields were determined. Muscle fiber type composition, Warner-Bratzler shear force, pH and color were determined in the longissimus lumborum muscle. In experiment I, energy restriction followed by ad libitum feeding affected lamb birth weight (P<0.05); however, no effects (P>0.05) were observed on later BW, REA, BF or carcass traits. Lambs born to non-restricted-fed ewes had higher (P<0.05) weight and yield of the frenched rack cut and their meat tended (P=0.11) to be tender compared with that of lambs from restricted ewes. The percentage of oxidative muscle fibers was lower for lambs born to non-restricted ewes (P<0.05); however, no effects of ewe treatment were observed on other muscle fiber types. For experiment II, energy restriction followed by ME requirements feeding, affected (P<0.01) pre-weaning live weight gain, weaning and final weights. Lambs from restricted ewes had higher (P<0.05) feed intake as % of leg weight and a trend to be less efficient (P=0.16) than lambs from unrestricted dams. Ribeye area and BF were not influenced by treatment. Treatment significantly affected slaughter weight, but had no effects on carcass yield and traits or on meat traits. The results obtained in both experiments indicate submitting ewes to energy restriction during gestation affects the performance of their progeny but the final outcome would depend on the ewe's re-feeding level during late gestation and the capacity of the offspring to compensate the in utero restriction after birth.
Keywords: feedlot; fetal programming; metabolizable energy